Environmental knowledge, actions and awareness – relationships with socio-economic factors - Trinh Thi Giang Thanh (Journal of Technical Education Science, 2014)
This subtle and small-sized study aims at testing the two most common assumptions on environmental awareness. An online survey was conducted in order to reach the aim. 211 participants were involved. The results of the survey reveal that there is no correlation between implicit knowledge and explicit actions for the environment. In addition, gender, family background and income – the three socio-economic factors to be included in the study – were tested for the dependence of environmental awareness. Statistics shows that environmental awareness is not significantly dependent on gender, family background and income. However, family background has significant influence on the level of knowledge about the environment. Participants with intellectual background have better environmental knowledge than the other groups. It is concluded that family is important in educating people about the environment.